Core needle biopsy versus fine needle aspiration cytology in bone and soft tissue tumors - Bharat Rekhi (Journal of Cytology, 2019)
Fine needle aspiration cytology (FNAC) for diagnosis of musculoskeletal tumors is well discussed and debated. The current evidence restricts its application in recurrent and metastatic lesions, with core needle biopsy as the acceptable technique/gold standard for the primary diagnosis of these challenging tumors. However, there are several studies showing reasonable sensitivity and specificity in primary diagnosis of bone and soft tissue tumors, especially in differentiating benign from malignant tumors. There is an acceptable limitation in the exact subtyping of soft tissue tumors, based on cytology smear examination, in the absence of ancillary techniques. Nonetheless, cytology constitutes an optimal material for triaging cases for ancillary techniques, such as immunocytochemistry, immunohistochemistry, molecular cytogenetics, and molecular diagnosis, in the form of smears and cell block preparations. This review focuses on the strengths and limitations of cytology versus core needle biopsy in the diagnosis of bone and soft tissue tumors, with the current evidence in the form of published studies, including the authors' experience.